2022-LBA-1183-ESGO Lymphedema appearance according to nodal staging in endometrial cancer. (27th October 2022) - García-Pineda, Virginia; Alonso-Espías, María; Arnedo, Rocío; Gracia, Myriam; Zapardiel, Ignacio; Siegrist, Jaime; Diestro, Maria Dolores; Hernández, Alicia
Abstract : Introduction: Sentinel lymph node (SLN) mapping has been demonstrated to be an accurate nodal staging method in early stage of endometrial cancer (EC), however, the advantage that it offers in patient's morbidity compared to systematic lymphadenectomy has not been extensively evaluated. The aim of our study is to compare the appearance of lymphedema according to nodal staging. Methods: A single institutional retrospective study was performed including all patients with early-stage endometrial cancer who underwent surgical nodal staging between January 2012 and December 2021. Patients with disseminated disease on imaging or at the time of surgery were excluded. All these patients underwent nodal staging with SLN mapping ± pelvic (PLD) and para-aortic (PALD) lymph node dissection. We evaluated lymphedema appearance separating the patients in two groups: group 1: SLN mapping; group 2: Systematic PLD±PALD with or without SLN mapping. Results: We evaluated a total of 270 patients, among them, 150 (55, 6%) underwent only SLN mapping (group 1) and 120 (44, 4%) received nodal staging by full lymphadenectomies (group 2: 107 (89, 1%) patients PLD+PALD and 13 patients (10, 9%) PLD alone. The main surgical approach was laparoscopy (260 patients (96.3%). A median (range) number of 2, 7 (0–9) sentinel nodes, 10, 9 (0–36) pelvic nodes and 12, 4 (0–39) paraaortic nodes were removed per patient. Comparing both groups, performing systematic lymphadenectomies was associated with greater risk of lymphedema (group 1: 0, 7%; group 2: 14, 3%, p<0, 001) with an odds ratio of 23.8 (95% confidence interval 3.1 to 182.7). Conclusions: SLN mapping is a safe and accurate alternative to complete lymphadenectomy in nodal staging of endometrial cancer with a lower risk of lymphatic complications. Our results support the use of SLN mapping improving the quality of life of patients with endometrial cancer.